Crimes Against Humanity : The Struggle for Global Justice - Robertson, Geoffrey (London Penguin Books, 2002)
This text explains what the rules of international human rights are, how they have developed, and in what courts and tribunals they may be asserted and vindicated. It discusses the development of human rights as philosophy, then as law.
Includes Appendix and Index.
Previous edition: London : Allen Lane, 1999.
Keywords: Human Rights -- Crimes Against Humanity -- War Crimes